PELAKSANAAN PEMBELAJARAN RANDAI PADA PENGEMBANGAN DIRI DI SMPN 14 PADANG - Gemala Dewi; Herlinda Mansyur; Darmawati Darmawati (FBS Universitas Negeri Padang, 2018)
Abstract This article aimed to find and describe the implementation of Randai Learning on Self-Development at SMPN 14 Padang. The type of this research was qualitative research. This research applied descriptive method. Data collection in the field was done by observation, interviews, and documentation. In addition, data were collected from library studies, observations, and interviews. The analysis of data was conducted by qualitative data analysis, and then the analysis was described and concluded. The results of the research showed that the implementation of Randai Learning on Self-Development at SMPN 14 Padang was influenced by factors that inhibited the effectiveness of Randai activities. These factors were internal and external factors. Internal factors consisted of urge factors, attention factors, and participation factors that came from the students themselves, while external factors of students included parents, teacher factors, and facility factors. These factors can be specified as follows: 1) Students did not always pay attention to the teacher and trainer. 2) Less interest in students in paying attention to teachers had an impact on students' lack of understanding of the mastery toward the material given. 3) The material for combining music with legaran based on dendang became difficult material for students because of the short time given and the distracted attention of students. 4) Lack of mastery of material that caused students unable to display what had been given well. Keywords: Randai and Self Development